Explanation:
Given mCDF = (3x + 14), mFDE = (5x - 2), and mCDE = (10x – 18)", then the expression mCDE = mCDF+mFDE is true.
To get x, we will substitute the given angles into the formula as shown;
(10x – 18) = (3x + 14)+ (5x - 2)
10x-18 = 3x+5x+14-2
10x-18 = 8x+12
10x-8x = 12+18
2x = 30
x = 30/2
x = 15
Find the measure of each angle
For mCDF:
mCDF = 3x + 14
mCDF = 3(15)+ 14
mCDF = 45+14
mCDF = 59°
For mFDE:
mFDE = (5x - 2)
mFDE = 5(15) - 2
mFDE = 75-2
mFDE = 73°
For mCDE:
mCDE = (10x – 18)
mCDE = 10(15) - 18
mCDE = 150-18
mCDE = 132°